Growth dynamics and allometric relationships of Passiflora species rootstocks - Morgado, Marcos Antônio Dell'Orto; Bruckner, Claudio Horst; Rosado, Luciana Domiciano Silva; Santos, Carlos Eduardo Magalhães dos (Comunicata Scientiae, 2017)
Passion fruit (Passiflora edulis Sims) is characterized by being a tropical fruit, with significant production in Brazil, however the occurrence of diseases, especially fungal infections that affects the root system, has reduced its production. Some Passifloraceae species are reported as being resistant to these pathogens, which feature in potential rootstock for P. edulis cultivation in contaminated areas, although the patterns of growth and development of these species has not being elucidated yet. Thus, the objective was to study the dynamics of growth and evaluate the dry matter distribution of passion fruit with potential rootstock use. Passiflora cincinnata, Passiflora mucronata, Passiflora giberti, Passiflora morifolia and Passiflora edulis (control) developed in polyvinyl chloride tubes of 100 mm in diameter and 150 cm in height, in order to assess plant height, leaf area, number of secondary roots, stem diameter, taproot lenght, root system volume, absolute growth rate, relative growth rate, net assimilation rate, leaf mass ratio and root mass ratio, at 30, 45, 60, 75, 90 and 105 days after transplanting. The species P. cincinnata, P. giberti and P. morifolia presented higher or similar growth rates than P. edulis for all evaluated characteristics, throughout the evaluation period. The root system of the species P. giberti and P. morifolia showed better distribution along the substrate. The species P. mucronata obtained lower growth than other species, both for the shoot and the root system.